Multiple sclerosis and eye: Geometric complexity of the optic nerve head microvascularity-a pilot study - G Bianciardi; C Traversi (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
Multiple Sclerosis (MS) is a progressive neurodegenerative disease of the central nervous system characterized by focal demyelinating lesions in the white matter of the brain or spinal cord. When MS affects the nerves in a person's eyes, it can cause Optic Neuritis (ON). We have investigated the microvascular pattern of the nerve head performing the evaluation of its fractal dimension (geometric complexity). Mean geometric complexity of the optic nerve head microvascularity in the affected eye in patients with multiple sclerosis resulted higher than in control normal subjects (p<0.01), and, moreover, the unaffected eye in patients with multiple sclerosis showed a geometric complexity that was not significantly different from the one of the affected eye and higher than in control normal subjects (p<0.01). These data, if confirmed in a higher number of patients, could show a characteristic microvascular pattern of the optic nerve head in subjects affected by multiple sclerosis, giving us a possible tool to identify earlier subjects that can develop multiple sclerosis.